2019
DOI: 10.1097/md.0000000000017283
|View full text |Cite
|
Sign up to set email alerts
|

Does cognitive-behavioral therapy reduce internet addiction? Protocol for a systematic review and meta-analysis

Abstract: Background:Cognitive-behavioral therapy has been considered as a means for internet addiction, but its long-term effect and the impact of internet addiction types and culture are still unclear.Objective:This study aims to assess the efficacy of cognitive-behavior therapy for internet addiction symptoms and associated other psychopathological symptoms.Method and analysis:We will search PubMed, Web of Knowledge, Ovid Medline, Chongqing Vip Database, Wanfang, and China National Knowledge Infrastructure database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
4
0
3
Order By: Relevance
“…Saat stres timbul, banyak diantara mahasiswa yang menggunakan internet secara berlebihan sehingga menyebabkan adiksi. 3 Saat ini ada beberapa metode yang digunakan untuk mewujudkan perbaikan adiksi internet 9 ataupun stres. Terapi ini memodifikasi perilaku melalui berbagai pendekatan yakni individu, kelompok, keluarga.…”
Section: -5unclassified
See 1 more Smart Citation
“…Saat stres timbul, banyak diantara mahasiswa yang menggunakan internet secara berlebihan sehingga menyebabkan adiksi. 3 Saat ini ada beberapa metode yang digunakan untuk mewujudkan perbaikan adiksi internet 9 ataupun stres. Terapi ini memodifikasi perilaku melalui berbagai pendekatan yakni individu, kelompok, keluarga.…”
Section: -5unclassified
“…Dalam hal ini, pengurangan gejala adiksi internet diperoleh tetapi terbatas oleh efek jangka panjang. 9 Song dan Park (2019) menemukan bahwa metode mindfulness memiliki peluang dalam menciptakan perbaikan stres maupun adiksi internet. 12 Pelatihan mindfulness dalam penelitian Romadhoni dan Widiatie (2020) menunjukkan adanya perbaikan stress pada remaja 13 sedangkan mindfulness parenting pada dilakukan terhadap orang tua.…”
Section: -5unclassified
“…Most individuals presenting with both substance-based and non-substance-based addictions have co-occurring mental health disorders, past traumas, and/or some level of functional impairments (e.g., cognitive, social) which may predict treatment outcome and appear to differ between addiction problems [ 5 , 6 ]. CBT is regarded as a ‘gold standard’ of psychotherapy in the treatment of most mental health including internet use-related addiction disorders [ 7 , 8 ]. However, current meta-analyses in the field of substance use disorders show that CBT can only be considered a preferred option for patients with comorbid anxiety and depression [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on CBT to reduce IA has shown that what is relevant for the user with an online addiction problem is understanding and evaluating the problematic event. In other words, cognitive reconstruction can support the transformation of the user’s negative thoughts to incorporate new meanings, feelings, and behaviours associated with online activities [ 7 ]. The modification of the cognitive and behavioural sphere that supports the unhealthy online habit requires a change in cognitive style (i.e., reconstruction), development of healthier and adaptable skills (i.e., skill-building), and acquisition of a new lifestyle (reorganising daily life).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation